2008
DOI: 10.1016/j.adolescence.2008.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Conflict negotiation and autonomy processes in adolescent romantic relationships: An observational study of interdependency in boyfriend and girlfriend effects

Abstract: This study examined the association between conflict negotiation and the expression of autonomy in adolescent romantic partners. Thirty‐seven couples participated in a globally coded conflict interaction task. Actor‐partner interdependence models (APIM) were used to quantify the extent to which boys’ and girls’ autonomy was linked solely to their own negotiation of the conflict or whether it was linked conjointly to their own and their partners’ negotiation style. Combining agentic autonomy theories and peer s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 35 publications
4
24
0
1
Order By: Relevance
“…The current study used an extant sample from a larger longitudinal study of adolescent relationships with mothers, close friends, and romantic partners (see Connolly et al 2015;McIsaac et al 2008). The current study consisted only of adolescents who participated in observation sessions with their mothers and/or close friends.…”
Section: Methods Participantsmentioning
confidence: 98%
“…The current study used an extant sample from a larger longitudinal study of adolescent relationships with mothers, close friends, and romantic partners (see Connolly et al 2015;McIsaac et al 2008). The current study consisted only of adolescents who participated in observation sessions with their mothers and/or close friends.…”
Section: Methods Participantsmentioning
confidence: 98%
“…Increasing involvement in a romantic relationship challenges partners to negotiate issues of autonomy and relatedness, learning to be sensitive to the other and to maintain a sense of self (Furman and Wehner 1997;McIsaac et al 2008). Within relationships, partners learn to express and regulate resentments, and to utilize disagreements as a means of improving the nature and course of a relationship.…”
Section: The Present Studymentioning
confidence: 97%
“…Foshee et al (2009) suggested that when females fail to get what they want from their partners, and when indirect forms of negotiating and teasing do not work, they employ more coercive, physically aggressive strategies. Other researchers have suggested that females have a greater need to establish autonomy in the emerging romantic relationship (McIsaac, Connolly, McKenney, Pepler, & Craig, 2008), which may result in more physical and relational aggression.…”
Section: Correlates Of Relationship Functioning In Adolescent Couplesmentioning
confidence: 98%